English Language Training for MSMEs: A Strategy to Improve Competitiveness in the Global Market - Veri Hardinansyah Dja'far (Transpublika Publisher, 2024)
This research aims to assess the effectiveness of English language training in improving the competitiveness of MSMEs, with a case study on My Zahro Collection, an MSME in the field of Muslim fashion. This research uses a qualitative descriptive method in the form of community service. Data was collected through observation, interviews, questionnaires, as well as pre-test and post-test to measure the improvement of participants' skills after the training. The training involved four main sessions, namely business communication in English, international business transactions, product description creation, and digital marketing strategies. The results showed that before the training, the majority of My Zahro Collection employees had limitations in business vocabulary (65% low category), speaking ability (70% low category), and understanding of digital marketing strategies (75% low category). After the training, there were significant improvements in each skill aspect, with understanding of digital marketing strategies increasing by 55%, ability to write product descriptions by 50%, speaking ability by 45%, and understanding of business vocabulary by 40%. In addition, 90% of participants felt more confident in communicating with international customers. This research confirms that practice-based English language training is effective in improving MSMEs' business communication skills. Hence, similar training programs need to be developed sustainably to support MSMEs in improving their global competitiveness.